Acidic electrolytic copper plating solution

CN122953338APending Publication Date: 2026-10-20MITSUBISHI MATERIALS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580019233.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-03-07
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0024]根据本发明,能够提供一种可通过镀覆法稳定地形成孔隙率高且晶体粒径小的多孔铜层的酸性电解镀铜液。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The acidic electrolytic copper plating solution is characterized by comprising soluble copper salts, azole compounds, carboxylic acids, water, and acids, wherein the content of the azole compounds is in the range of 5 mmol / L or more and 100 mmol / L or less, and the content of the carboxylic acids is in the range of 5 mg / L or more and 500 mg / L or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an acidic electrolytic copper plating solution used when forming a porous copper layer on the surface of a component.

[0002] This application claims priority based on Japanese Patent Application No. 2024-036201, filed on March 8, 2024, the contents of which are incorporated herein by reference. Background Technology

[0003] In recent years, the performance of semiconductor devices has been developing towards higher performance, and the importance of micro-junction technology is increasing.

[0004] As an IC chip mounting technology, flip chip mounting is widely used. For example, as shown in Patent Document 1, a method is provided to form a solder layer on a protruding electrode and bond it with solder.

[0005] Furthermore, for example, as shown in Patent Documents 1 and 2, bonding techniques such as the TLP method (Transient Liquid Phase Diffusion Bonding) and the SLID method (Solid-Liquid Interdiffusion) have been proposed, which bond the solid and liquid phases by interdiffusion.

[0006] As a next-generation mounting technology for even finer pitches, a technique for solid-state diffusion bonding of copper components has been proposed. In this case, when bonding substrates with multiple Cu pillars, precise alignment of the Cu pillars to be bonded is required, necessitating processing such as CMP.

[0007] Furthermore, for example, as shown in Patent Document 3, a technique is proposed to form a porous copper layer (preformed layer) on the bonding surface of Cu pillars and to solid-state diffusion bond the Cu pillars together. When pressure is applied during bonding, the porous copper layer (preformed layer) acts as a buffer, thereby enabling the bonded Cu pillars to contact each other and achieve bonding even if there is a deviation in the height of the Cu pillars.

[0008] Patent Document 1: Japanese Patent No. 6061276

[0009] Patent Document 2: Japanese Patent No. 6369620

[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-046148

[0011] However, when using porous copper layers to bond Cu pillars to each other, even if the height deviation of the Cu pillars is large, it is necessary to further increase the porosity in the porous copper layer in order to ensure that the Cu pillars can reliably contact each other.

[0012] Furthermore, to ensure the bonding strength after bonding, the porous copper layer requires a fine crystal grain size. Summary of the Invention

[0013] The present invention was made in view of the foregoing circumstances, and its object is to provide an acidic electrolytic copper plating solution that can stably form a porous copper layer with high porosity and small crystal grain size by plating method.

[0014] To address the aforementioned issues, the acidic electrolytic copper plating solution of aspect 1 of the present invention is characterized by comprising a soluble copper salt, an azole compound, a carboxylic acid, water, and an acid, wherein the content of the azole compound is in the range of 5 mmol / L or more and 100 mmol / L or less, and the content of the carboxylic acid is in the range of 5 mg / L or more and 500 mg / L or less.

[0015] According to aspect 1 of the present invention, the acidic electrolytic copper plating solution contains azole compounds in the range of 5 mmol / L or more and 100 mmol / L or less. Therefore, during electrolytic plating, the azole compounds are adsorbed together with copper ions on the cathode surface, thereby strongly inhibiting copper electrodeposition and preferentially promoting copper nucleation, thereby forming a porous copper layer composed of copper particles on the cathode surface.

[0016] Furthermore, in the acidic electrolytic copper plating solution of aspect 1 of the present invention, since carboxylic acid is present in the range of 5 mg / L or more and 500 mg / L or less, Cu ions form complexes with the carboxylic acid, further suppressing copper electrodeposition and thereby increasing the porosity of the porous copper layer. Moreover, the growth of precipitated copper particles is suppressed, enabling the formation of a porous copper layer with small crystal grain size.

[0017] Therefore, for example, even when there is a deviation in the height of the Cu pillars, it is possible to make the joined Cu pillars come into contact with each other and be firmly joined.

[0018] The acidic electrolytic copper plating solution of aspect 2 of the present invention is characterized in that, in the acidic electrolytic copper plating solution of aspect 1, the azole compound is a compound of the following formulas (1) to (4) having two or more but less than three nitrogen atoms in a five-membered ring.

[0019] [Chemical Formula 1]

[0020]

[0021] In the above formulas (1) to (4), R1 to R4 can be the same or different from each other, and can be any one of alkyl with 10 or less carbon atoms, alkenyl with 10 or less carbon atoms, alkynyl with 10 or less carbon atoms, aryl with 10 or less carbon atoms, aralkyl with 10 or less carbon atoms, and alkoxy with 10 or less carbon atoms, or can be a group obtained by replacing these hydrogen atoms with any one of halogen atom, hydroxyl, carboxyl, amino, alkyl-substituted amino with 5 or less carbon atoms, hydroxyalkyl-substituted amino with 5 or less carbon atoms in an alkyl chain, and mercapto, or can be any one of amino, alkyl-substituted amino with 5 or less carbon atoms, hydroxyalkyl-substituted amino with 5 or less carbon atoms in an alkyl chain, mercapto, hydroxyl, carboxyl, halogen atom, or hydrogen atom.

[0022] According to aspect 2 of the present invention, the acidic electrolytic copper plating solution contains compounds with structures shown in formulas (1) to (4) as azole compounds, which reliably suppress copper electrodeposition, thereby enabling the formation of a porous copper layer composed of copper particles on the cathode surface. Furthermore, since it contains carboxylic acid in the range of 5 mg / L to 500 mg / L, it is possible to reliably form a porous copper layer with high porosity and small average particle size.

[0023] Therefore, for example, even when there is a deviation in the height of the Cu pillars, it is possible to make the joined Cu pillars come into contact with each other and be firmly joined.

[0024] According to the present invention, an acidic electrolytic copper plating solution can be provided to stably form a porous copper layer with high porosity and small crystal grain size by plating. Attached Figure Description

[0025] Figure 1A This is an explanatory diagram illustrating a method for forming a porous copper layer using an acidic electrolytic copper plating solution according to an embodiment of the present invention, and is a schematic diagram of an electrolytic copper plating apparatus.

[0026] Figure 1B This is an explanatory diagram illustrating a method for forming a porous copper layer using an acidic electrolytic copper plating solution according to an embodiment of the present invention, and is a schematic side view of a substrate in which the porous copper layer is formed in a pattern.

[0027] Figure 2 This is an enlarged side view of a porous copper layer formed using an acidic electrolytic copper plating solution according to an embodiment of the present invention.

[0028] Figure 3 This is an explanatory diagram showing the process of manufacturing a bonding assembly using a porous copper layer.

[0029] Figure 4 This is an illustrative diagram showing a method for manufacturing a joint and measuring its shear strength in an embodiment.

[0030] Figure 5A This is a cross-sectional SEM (Scanning Electron Microscope) image of the porous copper layer observed in Example 1 of the present invention.

[0031] Figure 5B This is a cross-sectional SEM image of the porous copper layer observed in Comparative Example 1 of the embodiments.

[0032] Figure 5C This is a cross-sectional SEM image of the porous copper layer observed in Comparative Example 2 of the embodiment. Detailed Implementation

[0033] Hereinafter, an acidic electrolytic copper plating solution according to an embodiment of the present invention will be described with reference to the accompanying drawings.

[0034] The acidic electrolytic copper plating solution involved in this embodiment is used to form a porous copper layer, which is used, for example, in a semiconductor device, when multiple protruding electrodes (Cu pillars) disposed on a semiconductor chip or substrate are joined together.

[0035] The acidic electrolytic copper plating solution of this embodiment contains soluble copper salts, azole compounds, carboxylic acids, water, and acid. The content of azole compounds is in the range of 5 mmol / L or more and 100 mmol / L or less, and the content of carboxylic acids is in the range of 5 mg / L or more and 500 mg / L or less.

[0036] In addition, the acidic electrolytic copper plating solution of this embodiment may contain other components as needed, such as brighteners, surfactants, antioxidants, etc.

[0037] Specific examples of soluble copper salts include copper sulfate, copper oxide, and copper carbonate; alkane sulfonates such as copper methanesulfonate and copper propionate; alkane sulfonates such as copper hydroxyethanesulfonate and copper propanol sulfonate; and organic acid copper salts such as copper acetate, copper citrate, and copper tartrate. These can be used individually or in combination of two or more.

[0038] As acids, examples can be organic or inorganic acids. Here, acids may not include carboxylic acids. Examples include sulfuric acid; alkane sulfonic acids such as methanesulfonic acid and propanesulfonic acid; and alkane sulfonic acids such as hydroxyethanesulfonic acid and propanol sulfonic acid. These can be used individually or in combination of two or more.

[0039] Examples of water include ion-exchanged water and distilled water.

[0040] Examples of azole compounds include imidazole, 2-aminoimidazole, pyrazole, 3-aminoimidazole, 1,2,3-triazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, 3,5-diamino-1,2,4-triazole, and 3-amino-5-methylthio-1H-1,2,4-triazole. Furthermore, these azole compounds are those shown in formulas (1) to (4) above, having two or more but no more than three nitrogen atoms in a five-membered ring.

[0041] The imidazole mentioned above is one of the azole compounds shown in formula (1) above, as shown in formula (5) below.

[0042] 2-Aminoimidazole is one of the azole compounds shown in formula (1) above, as shown in formula (6) below.

[0043] Pyrazole is one of the azole compounds shown in formula (2) above, as shown in formula (7) below.

[0044] 3-Aminoimidazole is one of the azole compounds shown in formula (2) above, as shown in formula (8) below.

[0045] 1,2,3-triazole is one of the azole compounds shown in formula (3) above, as shown in formula (9) below.

[0046] [Chemical Formula 2]

[0047]

[0048] 1,2,4-Triazole is one of the azole compounds shown in formula (4) above, as shown in formula (10) below.

[0049] 3-Amino-1,2,4-triazole is one of the azole compounds shown in formula (4) above, as shown in formula (11) below.

[0050] 3,5-Diamino-1,2,4-triazole is one of the azole compounds shown in formula (4) above, as shown in formula (12) below.

[0051] 3-Amino-5-methylthio-1H-1,2,4-triazole is one of the azole compounds shown in formula (4) above, as shown in formula (13) below.

[0052] [Chemical Formula 3]

[0053]

[0054] Zyraxol compounds, during electroplating, adsorb onto the cathode surface along with copper ions, thus inhibiting copper electrodeposition and acting as copper ion electrodeposition inhibitors. In this way, by suppressing copper electrodeposition, copper nucleation preferentially occurs on the cathode surface, forming a porous copper layer composed of copper particles.

[0055] Examples of carboxylic acids include acetic acid, propionic acid, oxalic acid, citric acid, gluconic acid, and glycine.

[0056] The carboxylic acid forms a complex with Cu ions, further inhibiting copper electrodeposition and increasing the porosity of the porous copper layer. Furthermore, the growth of precipitated copper particles is suppressed, resulting in a porous copper layer with small crystal grain size.

[0057] The acidic electrolytic copper plating solution of this embodiment can be prepared by mixing the above-mentioned soluble copper salt, an azole compound having two or more but less than three nitrogen atoms in a five-membered ring as a copper ion electrodeposition inhibitor, a carboxylic acid, an acid, and water.

[0058] Here, in the prepared acidic electrolytic copper plating solution, the content of soluble copper salt is preferably 0.01 mol / L or higher.

[0059] A porous copper layer can be stably formed as a copper plating film as long as the content of soluble copper salt is above 0.01 mol / L. There is no particular upper limit to the content of soluble copper salt, and it can be 1 mol / L.

[0060] Furthermore, in the acidic electrolytic copper plating solution, the lower limit of the azole compound content is preferably 5 mmol / L or more, more preferably 10 mmol / L or more. The upper limit of the azole compound content is preferably 100 mmol / L or less, more preferably 30 mmol / L or less.

[0061] In the prepared acidic electrolytic copper plating solution, the content of azole compounds that act as inhibitors of copper ion electrodeposition is in the range of 5 mmol / L or more and 100 mmol / L or less.

[0062] If the concentration of azole compounds is less than 5 mmol / L, the effect of inhibiting copper ion electrodeposition is poor, and a porous copper layer cannot be stably formed as a copper plating film. Furthermore, if the concentration of azole compounds exceeds 100 mmol / L, excessive inhibition of copper ion electrodeposition occurs, causing the copper plating film to become brittle and its strength to deteriorate significantly. Alternatively, the azole compounds may be insoluble in the liquid and precipitate.

[0063] In the prepared acidic electrolytic copper plating solution, the content of carboxylic acid is in the range of 5 mg / L or more and 500 mg / L or less.

[0064] If the content of carboxylic acid is less than 5 mg / L or more than 500 mg / L, the porosity in the porous copper layer will not increase, and it may not be possible to refine the crystal grain size.

[0065] Furthermore, in the acidic electrolytic copper plating solution, the lower limit of the carboxylic acid content is preferably 10 mg / L or more, more preferably 50 mg / L or more. The upper limit of the carboxylic acid content is preferably 300 mg / L or less, more preferably 150 mg / L or less.

[0066] In addition, there are no particular restrictions on the concentration of water or acid, other than the soluble copper salts, azole compounds and carboxylic acids, in the prepared acidic electrolytic copper plating solution. However, it is preferable to adjust the pH of the acidic electrolytic copper plating solution to be in the range of 0 to 5, and more preferably to set the pH in the range of 1 to 3.

[0067] Next, use Figure 1A , Figure 1B and Figure 2 The method for forming a porous copper layer in a pattern on the surface of a substrate using the acidic electrolytic copper plating solution of this embodiment will be described.

[0068] like Figure 1A , Figure 1B As shown, the acidic electrolytic copper plating solution 3 of this embodiment is placed into the plating tank 2 of the electrolytic copper plating apparatus 1. A substrate 4a is placed in the acidic electrolytic copper plating solution 3, and a copper material 5 is placed facing one side of the substrate 4a. The surface of the substrate 4a is made of copper or nickel and has a resist film 4b formed in a pattern. Then, the substrate 4a is connected to a cathode 6, which serves as the cathode, and the copper material 5 is connected to an anode 7, which serves as the soluble anode, for electrolytic copper plating.

[0069] On the surface of substrate 4a, a resist film 4b having openings at predetermined intervals is pre-formed. Thus, a porous copper layer 8 composed of copper particles 12 is formed as a copper plating film within the openings of the resist film 4b formed on one side of substrate 4a.

[0070] Here, regarding the conditions for electrolytic copper plating in the acidic electrolytic copper plating solution 3, for example, a DC power supply is used, and the current density in the substrate 4a, which is the object to be plated, is set to 0.1 A / dm³. 2 ~5A / dm 2 The optimal value is 0.4 A / dm. 2 ~1.0A / dm 2 Set the liquid temperature to approximately 10℃~60℃, preferably to approximately 25℃~50℃, and perform air and jet agitation or oscillating agitation.

[0071] If electrolytic copper plating is performed under the above conditions, copper ions and azole compounds, which act as inhibitors of copper ion electrodeposition, are also adsorbed onto the cathode surface, which serves as the substrate 4a. Due to the presence of azole compounds, copper ion electrodeposition is strongly suppressed, copper nucleation is preferentially promoted, and a porous copper layer 8 composed of copper particles 12 is formed on the cathode surface as a copper plating film. Furthermore, through the formation of complexes between carboxylic acids and copper ions, the porosity of the porous copper layer 8 increases, and the crystal grain size decreases.

[0072] After electrolytic copper plating, the substrate 4a with a porous copper layer 8 formed is taken out from the acidic electrolytic copper plating solution 3, and the resist film 4b is removed.

[0073] Then, the substrate 4a is cleaned with solvents such as ethanol, water, and acetone, and dried using dry air in the atmosphere. Thus, as... Figure 1B As shown, a porous copper layer 8 is formed in a pattern on one side of the substrate 4a. Cu pillars are bonded to the porous copper layer 8 formed in a pattern.

[0074] In addition, to prevent surface oxidation, the substrate 4a with the porous copper layer 8 is preferably immersed in a rust inhibitor with benzotriazole and surfactant as the main components for a specified time.

[0075] Here, the thickness of the porous copper layer 8 formed on the surface of the substrate 4a is preferably in the range of 15 μm or more and 50 μm or less.

[0076] If the thickness of the porous copper layer 8 is 15 μm or more, the strength of the porous copper layer 8 itself can be ensured, and it is easy to process. On the other hand, if the thickness of the porous copper layer 8 is 50 μm or less, the porous copper layer 8 follows the unevenness of each surface of the substrate or electronic component described below during bonding, thereby improving the bonding strength of the bond.

[0077] And, as Figure 2 As shown, the porous copper layer 8 is formed in the form of an aggregate of copper particles 12 deposited on the surface of the substrate 4a. The average porosity of the porous copper layer 8 composed of these copper particles 12 is preferably in the range of 10% or more and 80% or less.

[0078] If the average porosity is above 10%, it ensures the availability of copper particles that facilitate the sintering of the porous copper layer 8, thus improving the sinterability of the copper particles. If the average porosity is below 80%, the porosity within the porous copper layer 8 will not be too high, ensuring both the strength of the porous copper layer 8 and the sinterability of the copper particles.

[0079] Furthermore, the average porosity is more preferably 15% or more. And more preferably, the average porosity is 70% or less.

[0080] The average porosity of the porous copper layer 8 was calculated by analyzing images of its cross-section using a scanning electron microscope. The arithmetic mean of the porosities (P) calculated by the following formula (A) was taken as the average porosity. Specifically, measurements were taken three times under different fields of view, and the average value of the calculated porosities was taken as the average porosity.

[0081] P (%) = (S2 / S1) × 100 (A)

[0082] In Equation (A), P is the porosity of the porous copper layer 8, S1 is the total area of ​​the porous copper layer 8, and S2 is the area of ​​the pore portion in the porous copper layer 8.

[0083] And, as Figure 2 As shown in the magnified image, the surface of copper particles 12 is coated with copper nanoparticles 12a having an average particle size smaller than that of copper particles 12.

[0084] Copper plating is performed using the acidic electrolytic copper plating solution 3 of this embodiment, causing azole compounds to adsorb onto the copper surface and form complexes with copper ions through carboxylic acids. This inhibits copper electrodeposition, and nucleation is preferentially carried out, forming copper nanoparticles 12a on the surface of copper particles 12. Due to this characteristic structure, when the porous copper layer 8 is pressurized, the copper particles easily sinter together to form a strong bonding layer.

[0085] Here, since the average particle size of copper nanoparticles is composed of fine copper particles and even finer nanoparticles, it is difficult to calculate the average particle size from microscopic images. Instead, the average particle size is calculated based on BET measurements. Thus, the average particle size of copper nanoparticles calculated based on BET measurements is preferably 50 nm or more and 300 nm or less. If the average particle size of copper nanoparticles is within this range, the copper particles are easier to sinter.

[0086] Furthermore, the average particle size of the copper nanoparticles is preferably in the range of 50 nm or more and 200 nm or less.

[0087] The average particle size of the copper nanoparticles was determined using the BET method for the porous copper layer 8. For the BET method, a substrate 4a with the porous copper layer 8 formed on it was cut to a specified size and filled into a measurement cell. Measurement was performed using the BET single-point method. The mass of the substrate 4a was subtracted from the measured value, and a conversion was performed based on the mass of the porous copper layer 8 itself. The particle size of the copper nanoparticles was calculated based on the calculated BET measurement value and the following formula (B). Furthermore, the coefficient 335.95 in the following formula (B) is a value calculated based on the theoretical values ​​of the density of copper, the surface area of ​​the copper nanoparticles, and the volume of the copper nanoparticles. The average particle size (d) of the copper nanoparticles was measured three times using the BET method, and the average value was taken.

[0088] d (nm) = 335.95 / (BET measured value (m)) 2 / g)) (B)

[0089] Next, a method for manufacturing a bonding body using a substrate 4a having a porous copper layer 8 will be described.

[0090] First, such as Figure 3 As shown in (a), a substrate 4a is prepared to have a porous copper layer 8 formed on its surface. As the component to be bonded, an electronic component 17 (silicon chip element, LED chip element, etc.) is prepared.

[0091] Next, as Figure 3 As shown in (b), an electronic component 17 is mounted on a porous copper layer 8 formed on the surface of the substrate 4a. In this state, the electronic component 17 and the substrate 4a, which are stacked via the porous copper layer 8, are heated in a heating furnace under a nitrogen atmosphere at a temperature of 250°C to 350°C for 1 to 30 minutes. Depending on the situation, bonding can be performed while applying a pressure of 1 MPa or more and 20 MPa or less to the substrate 4a and the electronic component 17 in the stacking direction.

[0092] Therefore, as Figure 3 As shown in (c), the porous copper layer 8 becomes the bonding layer 15, through which the substrate 4a and the electronic component 17 are bonded, thereby creating the bonding body 18.

[0093] According to the acidic electrolytic copper plating solution of this embodiment, which is configured as described above, since it contains azole compounds in the range of 5 mmol / L or more and 100 mmol / L or less, the azole compounds are adsorbed together with copper ions on the cathode surface during electrolytic plating. As a result, copper electrodeposition is strongly suppressed and copper nucleation is preferentially carried out, thereby forming a porous copper layer composed of copper particles on the cathode surface.

[0094] Furthermore, in the acidic electrolytic copper plating solution of this embodiment, since carboxylic acid is present in a concentration range of 5 mg / L to 500 mg / L, Cu ions form complexes with the carboxylic acid, further suppressing copper electrodeposition and increasing the porosity of the porous copper layer. Moreover, the growth of precipitated copper particles is suppressed, resulting in a porous copper layer with small crystal grain size.

[0095] Therefore, for example, even when there is a deviation in the height of the Cu pillars, it is possible to make the joined Cu pillars come into contact with each other and be firmly joined.

[0096] In the acidic electrolytic copper plating solution of this embodiment, when the azole compound is a compound shown in formulas (1) to (4) above, having two or more but less nitrogen atoms in a five-membered ring, copper electrodeposition can be reliably suppressed, thereby enabling the formation of a porous copper layer composed of copper particles on the cathode surface. Furthermore, since the carboxylic acid is present in a concentration range of 5 mg / L to 500 mg / L, a porous copper layer with high porosity and small average particle size can be reliably formed.

[0097] Therefore, for example, even when there is a deviation in the height of the Cu pillars, it is possible to make the joined Cu pillars come into contact with each other and be firmly joined.

[0098] The embodiments of the present invention have been described above, but the present invention is not limited thereto. Appropriate modifications can be made without departing from the technical concept of the present invention.

[0099] For example, in this embodiment, a case is described in which a porous copper layer 8 is formed in a pattern on the surface of the substrate 4a and an electronic component 17 is bonded through the porous copper layer 8. However, this is not a limitation, and the bonded component can be bonded through the porous copper layer.

[0100] Example

[0101] The results of the verification experiments conducted to confirm the effectiveness of the present invention will be described below.

[0102] First, as shown in Tables 1 and 2, the acidic electrolytic copper plating solution containing copper sulfate pentahydrate (a soluble copper salt), azole compounds, and carboxylic acids was adjusted. In addition to copper sulfate pentahydrate, azole compounds, and carboxylic acids, water and sulfuric acid were added to adjust the pH to 2.5.

[0103] A Si substrate was prepared, and a Ti layer (100 nm thick) and a Cu layer (500 nm thick) were sequentially sputtered onto its surface. Using the aforementioned acidic electrolytic copper plating solution, electrolytic copper plating was performed on the Si substrate with the Cu layer formed on its surface, resulting in a porous copper layer. The plating conditions were set as follows: bath temperature: 30°C, pH: 2.5, and current density: as described in Tables 3 and 4. Furthermore, the plating time was adjusted to achieve a porous copper layer thickness of 2 μm.

[0104] Furthermore, to determine the bonding strength of the bond, a substrate (5mm × 5mm, 3mm thick) and a copper chip (1mm × 1mm, 2mm thick) made of oxygen-free copper were prepared. A porous copper layer was formed on the surface of the substrate and the copper chip using the aforementioned acidic electrolytic copper plating solution. The plating conditions were set as follows: bath temperature: 30°C, pH: 2.5, and current density: as described in Tables 3 and 4. Additionally, the plating time was adjusted to achieve a porous copper layer thickness of 2μm.

[0105] Then, as Figure 4 As shown, a substrate and a copper chip are stacked in a manner where a porous copper layer formed on the substrate is in contact with a porous copper layer formed on the copper chip. The bonding is performed using a pressure heating bonding apparatus (manufactured by ALPHA DESIGN Co., Ltd.; HTB-MM) under the conditions of heating temperature: 300°C, heating time: 1 minute, pressure load: 10 MPa, and atmosphere: nitrogen, and a bonded body is obtained.

[0106] The porosity, average particle size, and shear strength of the obtained porous copper layer are evaluated below.

[0107] (Porosity)

[0108] Samples were collected from a Si substrate with a porous copper layer formed by electrolytic plating. The cross-section along the thickness direction of the porous copper layer was processed by CP (Cross-section Polishing) and observed by SEM. The porosity was calculated using Equation (A) by binarizing the 10,000x SEM image.

[0109] Cross-sectional SEM images of Example 1 and Comparative Examples 1 and 2 of the present invention are shown below. Figure 5A , Figure 5B , Figure 5C In Example 1 of this invention ( Figure 5A In Comparative Example 1, a porous copper layer was confirmed to have formed. On the other hand, in Comparative Example 1 (… Figure 5B Comparative Example 2 () Figure 5C In the study, it was confirmed that no porous copper layer had been formed.

[0110] (Average particle size)

[0111] The BET method was performed using an HM-model-1201 manufactured by Macsorb Corporation. A Si substrate with a porous copper layer was cut into 2 mm square pieces and filled into the measurement cell. Measurements were taken using the BET single-point method. The mass of the copper sheet was subtracted from the measured value, and a conversion was performed based on the mass of the porous copper layer itself. The particle size of the copper nanoparticles was calculated based on the calculated BET measurement value and the following formula (B).

[0112] Furthermore, the coefficient 335.95 in equation (B) below is a value calculated based on the theoretical values ​​of copper density, copper nanoparticle surface area, and copper nanoparticle volume. The average particle size (d) of the copper nanoparticles was determined three times using the BET method, and the average value was taken.

[0113] d (nm) = 335.95 / (BET measured value (m)) 2 / g))

[0114] (Shear strength)

[0115] The shear strength of the joint was determined using a shear strength evaluation tester (a joint tester manufactured by Nordson Advanced Technology K.K.; Dage Series 4000).

[0116] Regarding the shear strength measurement, the substrate of the bond was horizontally fixed, and a copper chip was pushed horizontally from a position 50 μm above the surface (top surface) of the bond layer. The strength of the copper chip at breakage was measured. The shearing tool moved at a speed of 0.1 mm / s.

[0117] [Table 1]

[0118]

[0119] [Table 2]

[0120]

[0121] [Table 3]

[0122]

[0123] [Table 4]

[0124]

[0125] In Comparative Example 1, which does not contain azole compounds and carboxylic acids, a porous copper layer could not be formed.

[0126] In Comparative Examples 2-4, no azole compounds were present, so a porous copper layer could not be formed.

[0127] In Comparative Examples 5-7 and 9-11, which do not contain carboxylic acid, the porosity is smaller and the average particle size is larger, and the shear strength is lower compared to the present invention examples with the same current density.

[0128] In Comparative Example 8, the content of carboxylic acid was high, at 600 mg / L. Compared with the present invention example with the same current density, the porosity was small, the average particle size was large, and the shear strength was low.

[0129] In Comparative Example 12, the carboxylic acid content was only 1 mg / L. Compared with the present invention example with the same current density, the porosity was small, the average particle size was large, and the shear strength was low.

[0130] In contrast, in Examples 1 to 15 of the present invention, compared with the comparative examples with the same current density, the porosity is large and the average particle size is small, the shear strength is high, and the bonding is excellent.

[0131] The results of the above confirmation experiments confirm that, according to the present invention, an acidic electrolytic copper plating solution can be provided to stably form a porous copper layer with high porosity and small crystal grain size through a plating method.

[0132] Symbol Explanation

[0133] 4a base plate

[0134] 8. Porous copper layer.

Claims

1. An acidic electrolytic copper plating solution, characterized in that, It contains soluble copper salts, azole compounds, carboxylic acids, water, and acids, among which... The content of the azole compound is in the range of 5 mmol / L or more and 100 mmol / L or less, and the content of the carboxylic acid is in the range of 5 mg / L or more and 500 mg / L or less.

2. The acidic electrolytic copper plating solution according to claim 1, characterized in that, The azole compounds are compounds represented by the following formulas (1) to (4) having two or more but no more than three nitrogen atoms in a five-membered ring. [Chemical Formula 1] In the above formulas (1) to (4), R1 to R4 can be the same or different from each other, and can be any one of alkyl with 10 or less carbon atoms, alkenyl with 10 or less carbon atoms, alkynyl with 10 or less carbon atoms, aryl with 10 or less carbon atoms, aralkyl with 10 or less carbon atoms, and alkoxy with 10 or less carbon atoms, or can be a group obtained by replacing these hydrogen atoms with any one of halogen atom, hydroxyl, carboxyl, amino, alkyl-substituted amino with 5 or less carbon atoms, hydroxyalkyl-substituted amino with 5 or less carbon atoms in an alkyl chain, and mercapto, or can be any one of amino, alkyl-substituted amino with 5 or less carbon atoms, hydroxyalkyl-substituted amino with 5 or less carbon atoms in an alkyl chain, mercapto, hydroxyl, carboxyl, halogen atom, or hydrogen atom.

Citation Information

Patent Citations

  • printer

    JP1985061276A

  • Pipe making machine

    JP1988069620A

  • Terminal structure, semiconductor device, electronic device, and method of forming terminal

    JP2018046148A

  • Game machine

    JP2024036201A